Poza śmierć, ku Niemożliwemu. Kiriłłow vs. Nietzsche - Kruszelnicki, Wojciech (Przestrzenie Teorii, 2014)
The aim of this paper is to critically analyze and evaluate the commonly held belief in philosophy and literary studies that suicidal Kirillov – a relentlessly intriguing character featured in Dostoevsky’s The Devils – voices and embodies the same ideas that were later to become characteristic of Friedrich Nietzsche’s thought. This analysis begins with a critical reading of Boris Evlampiev’s essay: Dostoevsky and Nietzsche: Toward a New Metaphysics of Man. Evlampiev’s presents Kirillov as an individual who showed the way to the full affirmation of earthly life, much earlier than Nietzsche’s Zarathustra, without resorting to religious faith or visions of paradise and salvation in the afterlife. The author of this article presents arguments against the view that Kirillov is the forerunner of Zarathustra. As this staged confrontation between Kirillov and Nietzsche/ Zarathustra unfolds and Kirillov’s would-be “Nietzschean” conduct and ideology are reviewed, numerous problems and doubts arise. As the analysis of Nietzsche’s and Kirillov’s approaches to the issue of death and the transience of human existence progresses, it reveals contradictions in Nietzsche’s thought which show that there is a need to re-evaluate Kirillov’s character. Eventually, the author reaches the conclusion that Kirillov’s dilemmas are much closer to those of Nietzsche than one would initially think.